Healthy villages : a guide for communities and community health workers - Howard, Guy (World Health Organization, 2002)
Health is determined by many factors, including income, environmental conditions - such as access to adequate sanitation and safe water supplies - individual behaviour, and health services. More than half of the world's population lives in villages and rural areas and most of those without access to safe water sources or basic sanitation are rural dwellers. Enabling rural populations to protect and improve their health is a major challenge worldwide. In response to this, an informal ''healthy villages'' movement has evolved. A healthy villages project promotes local actions by community member.